Kurikulum Adaptif dalam Pendidikan Islam Inklusif: Upaya Pemenuhan Kebutuhan Individu Peserta Didik - Ilzamul Khoir, Muhammad (Khatulistiwa Insight: Islamic Education and Learning, 2025)
This study aims to analyze the inhibiting factors in implementing adaptive curricula within inclusive Islamic education in Indonesia. The focus is to identify challenges faced by Islamic educational institutions in accommodating students with special needs. Using a qualitative case study approach, data were collected through interviews, observations, and documentation at several institutions. The findings reveal five main obstacles: limited resources, lack of teacher training, insufficient parental support, inadequate infrastructure, and misalignment between the curriculum and students’ needs. These factors significantly hinder the effectiveness of adaptive curriculum implementation. The study recommends improving teacher training quality, providing sufficient resources, and developing a more flexible and inclusive curriculum. These efforts are expected to contribute to the advancement of more inclusive and high-quality Islamic education that is responsive to the diversity of learners.